The Host Factor: Understanding Childhood Poisoning - Abd Razak, Dzulkifli (1995)
"A CHILD LEARNS BY DOING. HE GAINS experience by investigating the world around him. For his experiences to be constructive they must be conducted in an environment where hazards are kept to a minimum..." It come to no suprise that children have long been considered to be the 'perfect host' in cases of poisoning. In fact poisoning involving common household substances, including medicines, a major cause of injuries among children. In the United States, it has been reported that more than 12,000 deaths due to poisoning occur each year mostly involving children. Data from the American Association of Poison Control Centers indicated that more than half of the poison exposure cases are in the one to five age group.